Determination of Proximate Composition of Local Corn Cultivar from Kisar Island, Southwest Maluku Regency - Hermalina Sinay; Nunung Harijati (Biosaintifika: Journal of Biology & Biology Education, 2021)
As a staple food, which consumed by many peoples in almost all places world wide, corn (Zea mays L.) has become very important. As well as in Indonesia, especially in Kisar Island, Southwest Maluku regency, corn already be the one of the most important food crops. The purpose of this study was to determine proximate content of local corn kernels from Kisar Island Maluku. Proximate analysis included content of water, fat, protein, ash, crude fiber, total carbohydrate and total sugar. Data collected are presented in form of table and analyzed descriptively. The data obtained were compared to the Indonesian national standard (SNI) of proximate content for corn kernels as well as to other results that have been reported by several researchers. The results of seven local corn cultivars from Kisar Island were in accordance with SNI standards about content of ash (1.13-2.04%), protein (9.14-13.02%), crude fiber (2.17 - 2.72%), fat (3.47-5.10% ), total carbohydrate (69.7 % -75.74%), and total sugar (58.66% -68.7%). The novelty of this research is to reveal the proximate content of local corn kernels from Kisar Island. This research is expected to be useful as a source of information about the proximate content of local corn seeds, and for instance it can be considered in the utilization and development of local corn in Kisar Island.